2021
DOI: 10.3934/neuroscience.2021018
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-dermatological association between psoriasis and depression: an immune-mediated inflammatory process validating skin-brain axis theory

Abstract: Objective Our study's motive was to recognize various immune-mediated inflammatory processes involved in the pathogenesis of depression and psoriasis and interlink between them based on inflammatory mediators. Methods A careful and comprehensive literature search was done through various databases like PubMed, Google Scholar, and EBSCO. A total of 56 studies were included in our study after careful screening. Results The immune-mediated infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
0
10
0
1
Order By: Relevance
“…The clinical presentations of PV include scaly itching, oedema, fatigue, burning, and erythema. In addition to the physical manifestations, this disease has also been linked with a decline in mental state, leading to suicidal thoughts and an overall deterioration in quality of life [5,6]. Current treatment interventions for PV include topical corticosteroids, phototherapy, and systemic therapies, based on the severity of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical presentations of PV include scaly itching, oedema, fatigue, burning, and erythema. In addition to the physical manifestations, this disease has also been linked with a decline in mental state, leading to suicidal thoughts and an overall deterioration in quality of life [5,6]. Current treatment interventions for PV include topical corticosteroids, phototherapy, and systemic therapies, based on the severity of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The mean CD4 + /CD8 + ratio in the model group was about 2.4, which was significantly higher than that of the normal group, indicating a representative characteristic of immune disorder in the IMQinduced psoriasis model. 72 The significantly reduced CD4 + / CD8 + ratios in EGCG-HP and MTX/EGCG-HP groups compared to the model group showed that the sustained release of EGCG led to good treatment outcomes (Figure S26a). Moreover, the percentage of CD11c + dendritic cells in the model group (35.7%) was much higher than the normal group (16.4%).…”
Section: Resultsmentioning
confidence: 97%
“…Our findings that rs925946 showed a strong association with obesity, however, supports the theory that BDNF may indeed be involved in linking obesity with psoriasis in the early-onset group of patients. Further findings—that the blood levels of BDNF were found to be reduced not only in psoriasis but also in depression, and thus may link major depression with psoriasis—call for studies to also integrate BDNF into psycho-dermatology [ 67 , 68 , 69 ]. However, the stigma of depression, which is similar to what we experience in regard to alcohol consumption [ 70 ], greatly limits the data collection for such studies.…”
Section: Discussionmentioning
confidence: 99%